Hubungan Dukungan Suami Dengan Kepatuhan Konsumsi Tablet Tambah Darah Pada Ibu Hamil di Wilayah Kerja Puskesmas Penanggalan Provinsi Aceh Tahun 2023 - Ariska Fauzianty; Fatrika Ulfa Irsal; Nova Isabella Mariance Br Napitupulu; Sonia Novitasari (Pusat Riset dan Inovasi Nasional, 2024)
Anemia during pregnancy is still a global problem throughout the world. Prevention of anemia in pregnant women can be done by increasing compliance with the consumption of blood supplement tablets. Pregnant women need motivation and support from husband during pregnancy. This reseach aims to explore the relationship between husband’s support with compliance with the consumption of blood supplement tablets in the Puskemas Penanggalan Provinsi Aceh in 2023. This research uses a quantitative method with a cross sectional approach. Data analysis used the Chi Square methods. This research was conducted in the work area with a total of 52 pregant women with purposive sampling. The research are the majority of respondents with aged 26-35 years were 20 people (46,5%), the majority of pregnant women get husband’s support were 22 people (57,7%). The results of chi square test, p value = 0,003, there is a significant relationship between husband’s support with compliance consumes iron acid. Midwives are expected to be able to place more emphasis on counseling regarding nutritional intake during pregnancy by using the contents of my plate media, choosing simpler words and language to further optimize continuous educational media during counseling, so that pregnant women can more easily understand the counseling given and provide leaflets containing about the contents of my plate so that pregnant women can read and understand it